Effect of parallax distribution and crosstalk on visual comfort in parallax barrier autostereoscopic display - Kim, Donghyun; Lee, Hyoung; Kim, Sung-Kyu; Sohn, Kwanghoon (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2015)
Although autostereoscopic display is considered to be mainstream in the three-dimensional (3-D) display market for the near future, practical quality problems still exist due to various challenges such as the accommodation-vergence conflict and crosstalk. A number of studies have shown that these problems reduce the visual comfort and reliability of the perceived workload. We present two experiments for investigating the effect of parallax distribution, which affects the behavior of the accommodation and vergence responses and crosstalk on visual comfort in autostereoscopic display. We measured the subjective visual scores and perceived depth position for watching under various conditions that include foreground parallax, background parallax, and crosstalk levels. The results show that the viewers' comfort is significantly influenced by parallax distribution that induces a suitable conflict between the accommodation and vergence responses of the human visual system. Moreover, we confirm that crosstalk changes significantly affect visual comfort in parallax barrier autostereoscopic display. Consequently, the results can be used as guidelines to produce or adjust the 3-D image in accordance with the characteristics of parallax barrier autostereoscopic display. c 2015 Society of PhotoOptical Instrumentation Engineers (SPIE)